Enhanced impact resistance of three‐dimensional woven composites with double‐layer core structure. Issue 4 (1st February 2023) - Yang, Xiaori; Zheng, Liangang; Chen, Long; Xu, Fujun
Abstract: In this study, to further improve the anti‐impact property of 3D woven spacer composites (3DWSC), three kinds of integrated 3DWSC with double‐layer cores assembled at different height combinations of 4 + 8 mm, 6 + 6 mm, and 8 + 4 mm, were designed and prepared. And the impact performances and the post‐impact lateral compressive properties of the resulting composites were investigated and compared to the single‐layer 3DWSC of the same height. The results show that among the three combinations, 3DWSC‐4 + 8 has the highest contact force value of 2454.33 N at 10 J, which is 90.60% higher than that of single‐layer 3DWSC. And the residual compressive strength of 3DWSC‐4 + 8 maintains 91.30% after 10 J energy impact, while the retention value of single‐layer 3DWSC is only 68.43%. The above results can be attributed to the fact that the addition of the middle panel in double‐layer 3DWSC is benefical to improve the capacity of the material to withstand transverse load or bending moment and to absorb more energy through its damage compared to the single‐layer 3DWSC. In addition, the SEM images showed that only resin cracks in the double‐layer 3DWSC and no fiber breakage and delamination, indicating exceptional mechanical stability of the as‐prepared double‐layer 3DWSC. This work can serve as a reference for the design and fabrication to multi‐layer 3DWSC, a promising material in the field of high‐performance composites. Abstract : Structural schematical diagram of 3DWSF‐12 and 3DWSF‐4+8. Contact force‐time curves at 10 J impact energy and lateral compressive strength. The addition of the middle panel could make the load uniformly distributed, and more energy can be absorbed.